Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Sites for CO2 activation over amine-functionalized mesoporous Ti(Al)-SBA-15 catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2006)
{Activation of CO and its utilization in the synthesis of chloropropene and styrene carbonates over functionalized, mesoporous SBA-15 solids, have been investigated. The surface basicity of SBA-15 was modified with nitrogen-based organic molecules of varying basicity viz., alkyl amines (-NH2), adenine (Ade), imidazole (Im) and guanine (Gua). The surface of SBA-15 was also functionalized with Ti4+ and Al3+ species. The acid-base properties of these modified SBA-15 materials were investigated by temperature-programmed desorption (TPD) and diffuse-reflectance infrared Fourier transform (DRIFT) spectroscopy. NH3 and pyridine were used as probe molecules for acid sites, while CO, was used to characterize the basic sites. CO was activated at the basic amine sites forming surface carbamate species (IR peaks: 1609 and 1446 cm(-1)). The latter reacted further with epoxides adsorbed on the acid sites forming cyclic carbonates. A correlation between the intensity of the IR peak at 1609 cm(-1) and cyclic carbonate yield has been observed. The cyclic carbonate yields were higher when both the acid and base functionalities were present on the surface. The Ti- and Al-SBA-15 functionalized with adenine exhibited the highest catalytic activity and selectivity. There is an optimal dependence (''
Keywords: aromatization; Ga-based zeolites; propane; Si/Al ratio; Si/Ga ratio; zeolitic factors